Premature luteinization and cumulus cell defects in ovarian-specific Smad4 knockout mice. - Pangas, SA; Li, X; Robertson, E; Matzuk, M (2006)
SMAD4 is a central component of the TGFbeta superfamily signaling pathway. Within the ovary, TGFbeta-related proteins play crucial roles in controlling granulosa cell growth, differentiation, and steroidogenesis. To study the in vivo roles of SMAD4 during follicle development, we generated an ovarian conditional knockout of Smad4 using the cre/loxP recombination system. Smad4 ovarian-specific knockout mice are subfertile with decreasing fertility over time and multiple defects in folliculogenesis. Regulation of steroidogenesis is disrupted in the Smad4 conditional knockout, leading to increased levels of serum progesterone. In addition, severe cumulus cell defects are present both in vivo and when assayed in vitro. These findings demonstrate that disrupting signaling through SMAD4 in the ovarian granulosa cells leads to premature luteinization of granulosa cells and eventually premature ovarian failure, thereby demonstrating key in vivo roles of TGFbeta superfamily signaling in the timing of granulosa cell differentiation.